Battle For Środkowopomorskie Voivodeship – Yesterday And Today (Research Bulletins of the Faculty of Economic Sciences, 2017)
The aim of the article is to discuss the next stages of the battle for the establishment of Środkowopomorskie voivodeship. Time scope of the study includes the years 1997 - 2016, period just before the administrative reform in 1999 until today. Separation of the administrative region of Middle Pomerania is needed for many reasons, both social and economic. The creation of Środkowopomorskie voivodeship could prevent the marginalization of the region and its communities, which take place in the current administrative division.
Keywords: Środkowopomorskie voivodeship; Middle Pomerania; changes in the territorial division